Historical Process of Medicine in Colombia from Pre-Columbian Cultures (1492-2008) - Ramírez Tamayo, Amparo Aurora; Olivella Jacquin, Juan Luciano; Ospino Castro, Luis Carlos (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
History of Medicine is a subject enrolled in undergraduate medical program of the Cooperative University of Colombia. Failing to find a book with the information needed to know some details of the process, we proceeded to solve the problem from the research considering the Columbian drug found by the Spaniards in the indigenous, the process of their development and academic study obtained students with European influence. Equally it researched the medical scientific progress achieved by the Colombians, outstanding, both in his native country and overseas doctors. The result shall be recorded in educational-academic text for the class of History of Medicine.